Increased frequency of co-existing JAK2 exon-12 or MPL exon-10 mutations in patients with low JAK2V617F allelic burden. Issue 6 (2nd June 2016) - Nussenzveig, Roberto H.; Pham, Ha T.; Perkins, Sherrie L.; Prchal, Josef T.; Agarwal, Archana M.; Salama, Mohamed E.
Abstract: The frequency of co-existing JAK2 V617F / MPL and JAK2 V617F / JAK2 exon-12 mutations has not been previously investigated in MPNs. Poor survival was reported in primary myelofibrosis with low JAK2 V617F allelic burden. However, mutational status of JAK2 exon-12 or MPL were not reported in these patients. This study developed a cost-effective multiplex high resolution melt assay that screens for mutations in JAK2 gene exons-12 and -14 ( V617F ) and MPL gene exon-10. Co-existing mutations with JAK2 V617F were detected in 2.9% (6/208; two JAK2 exon-12 and four MPL exon-10) patient specimens with known JAK2 V617F (allelic-burden range: 0.1–96.8%). Co-existing mutations were detected in specimens with < 12% JAK2 V617F allelic burden. Current WHO guidelines do not recommend further testing once JAK2 V617F mutation is detected in MPNs. The findings, however, indicate that quantification of JAK2 V617F allele burden may be clinically relevant in MPNs and in those with low allelic burden additional testing for JAK2 exon-12 and MPL exon-10 mutation should be pursued.